Interdisciplinary Radical “En-Bloc” Resection of Ewing Sarcoma of the Chest Wall and Simultaneous Chest Wall Repair Achieves Excellent Long-Term Survival in Children and Adolescents - Basharkhah, Alireza; Lackner, Herwig; Karastaneva, Anna; Bergovec, Marko; Spendel, Stephan; Castellani, Christoph; Sorantin, Erich; Benesch, Martin; Liegl-Atzwanger, Bernadette; Smolle-Jüttner, Freyja-Maria; Urban, Christian; Höllwarth, Michael; et al. (Frontiers in Pediatrics, 2021)
Introduction: Ewing sarcomas of the chest wall, historically known as “Askin tumors” represent highly aggressive pediatric malignancies with a reported 5-year survival ranging only between 40-60% in most studies. Multimodal oncological treatment according to specific Ewing sarcoma protocols and radical “en-bloc” resection with simultaneous chest wall repair are key factors for long-term survival. However, the surgical complexity depends on tumor location and volume and potential infiltrations into lung, pericardium, diaphragm, esophagus, spine and major vessels. Thus, the question arises, which surgical specialties should join their comprehensive skills when approaching a child with Ewing sarcoma of the chest wall. Patients and Methods: All pediatric patients with Ewing sarcomas of the chest wall treated between 1990 and 2020 were analyzed focusing on complete resection, chest wall reconstruction, surgical complications according to Clavien-Dindo (CD) and survival. Patients received neo-adjuvant chemotherapy according to the respective Ewing sarcoma protocols. Depending on tumor location and organ infiltration, a multi-disciplinary surgical team was orchestrated to perform radical en-bloc resection and simultaneous chest wall repair. Results: Thirteen consecutive patients (seven boys and six girls) were included. Median age at presentation was 10.9 years (range 2.2 to 21 years). Neo-adjuvant chemotherapy (n=13) and irradiation (n=3) achieved significant reduction of the median tumor volume (305.6 ml vs. 44 ml, p<0.05). En-bloc resection and simultaneous chest wall reconstruction was achieved without major complications despite multi-organ involvement. Postoperatively, one patient with infiltration of the costovertebral joint and laminectomy required surgical re-intervention (CD IIIb). 11/13 patients were treated with clear resections margins (R1 resection in one patient with infiltration of the costovertebral joint and marginal resection less than 1 mm in one child with multiple pulmonary metastases). All patients underwent postoperative chemotherapy; irradiation was performed in four children. Two deaths occurred 18 months and 7.5 years after diagnosis, respectively. Median follow-up for the remaining patients was 8.8 years (range: 0.9-30.7 years). The 5-year survival rate was 89% and the overall survival 85%. Conclusion: EWING specific oncological treatment and multi-disciplinary surgery performing radical en-bloc resections and simultaneous chest wall repair contribute to an improved survival of children with Ewing sarcoma of the chest wall.